Kinematic and physiological determinants of maximal skiing speed in the skating and classical style - Stöggl,T.; Müller, E. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Regarding WC sprint races, a steady increase in skiing velocity in both techniques can be stated, This might be a result of an upcoming specialization of athletes on the sprint, and of technical modifications for the sprint. To date only Holmberg et al. (2005) have demonstrated a so-called "sprinter-like" double poling (DP) technique. Biomechanical data for the diagonal stride (DIAG) and skating technique is lacking. Stöggl et al. (2007) have shown that maximal skiing speed was highly related to sprint performance. Additionally it was suggested that faster skiers produced longer cycle lengths (CL) at lower cycle rates (CR) in maximal speed tests in DP and DIAG. The purpose was to get information on kinematic and physiological determinants of maximal skiing speed in the skating and classic technique.